P007 Autoantibodies' titre changes during anti-BLyS treatment in systemic lupus erythematosus. (March 2019) - Cavazzana, I; Pozzari, C; Kumar, R; Ottaviani, R; Fredi, M; Piantoni, S; Tincani, A; Franceschini, F
Abstract : Career situation of first and presenting author: Assistant. Introduction: Belimumab, a human monoclonal antibody anti-soluble B lymphocytes stimulator, is the only biological drug approved for Systemic Lupus Erythematosus (SLE). It reduces disease activity and blocks damage progression. 1 2 Anyway, no definitive results have been published regarding its effect on autoantibodies' titre. Objectives: To analyse the modulation of anti-dsDNA, anti-ENA and anti-phospholipid antibodies' titre by Belimumab in patients affected by SLE. Methods: 50 SLE 3 patients starting Belimumab were enrolled. Sera were collected at baseline (T0) and every 6 months until 24th month. Clinical features and disease activity index (namely SLEDAI-2K) 4 were collected at any timepoints. AntidsDNA were analysed by radioimmunological method, anti-cardiolipin (aCL) and anti-β2 glycoprotein I (anti-β2GPI) were detected by home-made ELISA. 4 5 Anti-ENA were detected by ELISA; positive sera were further characterized by ELISA to identify anti-Ro, anti-La, anti-ribosomal P protein (ribP), anti-Sm and anti-U1RNP specificities. Results: At T0 anti-dsDNA were positive in 86%, anti-ENA in 50%, a CL in 20% and antibeta2GPI in 28% of cases, respectively. A negative seroconversion was detected in 9/43 anti-dsDNA (21%); in 5/12 anti-beta2GPI IgG (40%) and in 3/10 aCL IgG (30%) sera, mostly at T6. Among anti-ENA specificities 6/10 (60%) anti-ribP and 3/17 (17, 6%) anti-Sm positive sera became negative; while anti-Ro and anti-U1RNP antibodies resulted stable during treatment. A significant decrease of anti-dsDNA titre was observed at T6 (p 0, 0011); T12 (p: 0, 014); T18 (p: 0, 0031) and T24 (p: 0, 013). Anti-beta2GPI IgM isotype showed significant reduction at T6 (p: 0, 0032), T12 (0, 001), T18 (p: 0, 002) and T24 (p: 0, 011). ACL antibodies showed significant decrease only for IgG isotype at T18 (p: 0, 001). Anti-ribP antibodies showed a significant titre decrease at T6 (p: 0, 015) and T12 (p:0, 0078), with complete negative seroconversion at T18. Anti-Sm antibodies significantly dropped down at T6 (p:0.032), than maintained a stable titre during time. A significant correlation between anti-dsDNA titre anti-ribP titre and between SLEDAI ratio (SLEDAI value/SLEDAI T0) and anti-ribP ratio (value/value T0) were found. Conclusions: Belimumab treatment induced a significant reduction of high-affinity anti-dsDNA, anti-Sm and anti-ribP antibodies titre. The decrease of anti-ribP titre correlates with anti-dsDNA titre and disease activity. References: Ginzler EM, et al. J Rheumatol 2014;41:2. Iaccarino L, et al. Arthritis care Res 2017;69:115–123. Petri M, et al. Arthritis Rheum 2012;64:2677–86. Gladman DD, et al. J Rheumatol 2002;29:288–91. Harris EN. Ann J Clin Pathol 1990;94:476–84. Balestrieri G, et al. Lupus 1995;4:122–30. Disclosure of Interest: None declared.